2014
DOI: 10.1007/s10585-014-9658-1
|View full text |Cite
|
Sign up to set email alerts
|

Ascites-induced shift along epithelial-mesenchymal spectrum in ovarian cancer cells: enhancement of their invasive behavior partly dependant on αv integrins

Abstract: At least one-third of patients with epithelial ovarian cancer (OC) present ascites at diagnosis and almost all have ascites at recurrence. The presence of ascites, which acts as a dynamic reservoir of active molecules and cellular components, correlates with the OC peritoneal metastasis and is associated with poor prognosis. Since epithelial-mesenchymal transition (EMT) is involved in different phases of OC progression, we have investigated the effect of the unique ascitic tumor microenvironment on the EMT sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 48 publications
2
47
1
Order By: Relevance
“…1 Epithelial ovarian cancer metastasis is characterized by a spread of tumor cells within the peritoneal cavity and their subsequent invasion and proliferation within the organs of the pelvis. 4,5 These adhesion-related events are partly dependant on αv integrins, 6 specifically αvβ3, 7,8 which belongs to a family of cell surface integrin receptors.…”
Section: Introductionmentioning
confidence: 99%
“…1 Epithelial ovarian cancer metastasis is characterized by a spread of tumor cells within the peritoneal cavity and their subsequent invasion and proliferation within the organs of the pelvis. 4,5 These adhesion-related events are partly dependant on αv integrins, 6 specifically αvβ3, 7,8 which belongs to a family of cell surface integrin receptors.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with previous findings. Carduner et al 19 reported that αv had an important role in ovarian cancer progression. Lessan et al 20 informed that β1 integrin may responsible for adhesion of ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ascites have been shown to enhance epithelial to mesenchymal transition (EMT) in ovarian cancer cells. 8,41,42 During EMT, a stationary epithelial cell transforms into a mesenchymal cell capable of motility. This transition is an important precursor for metastasis and chemoresistance.…”
Section: A the Ovarian Cancer Mechanical Microenvironmentmentioning
confidence: 99%